P11.12 Periostin is expressed by pericytes and is crucial for angiogenesis in glioma. (6th September 2019) - Huizer, K; Kros, J M; Zhu, C; Chirifi, I; Krist, B; Cheng, C; Mustafa, D
Abstract: BACKGROUND: The expression of the matricellular protein periostin has recently been associated with glioma progression and angiogenesis. The aim of the present study was to identify the cellular source of periostin expression in human gliomas and to study the role of periostin in an in vitro model for angiogenesis. MATERIAL AND METHODS: The expression of periostin in various types and grades of brain tumors was investigated at the genetics level by RT-PCR and at the protein level by immunohistochemistry. In addition, the expression of periostin in glioma samples was studied by double labeling and in situ RNA techniques. Subsequently, by silencing periostin in a 3D in vitro angiogenesis model, its effects on angiogenesis were studied. RESULTS: Periostin RNA and protein expression was found to be elevated in pilocytic astrocytoma and glioblastoma, but not in grade II/III astrocytomas. The expression of periostin co-localized with PDGFRβ + cells, but not with Olig2+ / Sox2+ glioma stem cells. Silencing of periostin in pericytes resulted in the attenuation of the number and the length of the vessels, and in decrease in the number of vessel junctions formed. CONCLUSION: The results prove that pericytes are the main source of periostin in human gliomas. We demonstrate that periostin plays an essential role in the growth and branching of blood vessels. Therefore, periostin and / or its molecular interactions should be explored as a novel target for developing a new anti-angiogenic therapy for glioma.